2015
DOI: 10.1002/wsb.524
|View full text |Cite
|
Sign up to set email alerts
|

Retained satellite information influences performance of GPS devices in a forested ecosystem

Abstract: Global Positioning System (GPS) units used in animal telemetry often suffer from nonrandom data loss and location error. GPS units use stored satellite information to estimate locations, including almanac and ephemeris data reflecting satellite positions at weekly and at <4‐hr temporal scales, respectively. Using the smallest GPS collars (45–51 g) available for mammals, we evaluate how satellite information and environmental conditions affected GPS performance in 27 mobile trials, and field reliability during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…The GPS collars attempted a location every 5 minutes. To save battery life, we programmed GPS collars to collect locations only when martens were active (Moriarty and Epps ). We restricted our movement analyses to GPS locations with average predicted accuracy and standard error (SE) of 28 ± 7 m (Moriarty and Epps ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GPS collars attempted a location every 5 minutes. To save battery life, we programmed GPS collars to collect locations only when martens were active (Moriarty and Epps ). We restricted our movement analyses to GPS locations with average predicted accuracy and standard error (SE) of 28 ± 7 m (Moriarty and Epps ).…”
Section: Methodsmentioning
confidence: 99%
“…To save battery life, we programmed GPS collars to collect locations only when martens were active (Moriarty and Epps ). We restricted our movement analyses to GPS locations with average predicted accuracy and standard error (SE) of 28 ± 7 m (Moriarty and Epps ). We included only martens that were >2 years old in our sample because we were interested in the movement behavior of the segment of the population most likely to affect sustainability (Buskirk et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During non DLW-enrichment deployments, collars often suffered battery failure before the animal was re-captured (Moriarty and Epps 2015), resulting in differences in length of time monitored. Because martens often traverse the perimeter of their territories in fewer than five days, we considered our estimates of use areas representative of general space use.…”
Section: Movement Characteristics and Use Areasmentioning
confidence: 99%
“…However, past studies have primarily relied on ground telemetry and arguably provided sparse and temporally biased data. Although some studies have fitted small carnivores with GPS collars, recent sampling revealed numerous technical issues (Moriarty and Epps ). An understanding of habitat use, however, is critical for the marten, which is considered a focal species of forest management in eastern North America (Thompson , Hepinstall and Harrison ).…”
mentioning
confidence: 99%